Effect of formate on volume reabsorption in the rabbit proximal tubule. - Schild, L (1987)
Studies on microvillus membrane from rabbit kidney cortex suggest that chloride absorption may occur by chloride/formate exchange with recycling of formic acid by nonionic diffusion. We tested whether this transport mechanism participates in active NaCl reabsorption in the rabbit proximal tubule. In proximal tubule S2 segments perfused with low HCO-3 solutions, the addition of formate (0.25-0.5 mM) to the lumen and the bath increased volume reabsorption (JV) by 60%; the transepithelial potential difference remained unchanged. The effect of formate on JV was completely reversible and was inhibited both by ouabain and by luminal 4,4'-diisothiocyanostilbene-2,2'-disulfonate. Formate (0.5 mM) failed to stimulate JV in early proximal convoluted tubules perfused with high HCO-3 solutions. As measured by miniature glass pH microelectrodes, this lack of formate effect on JV was related to a less extensive acidification of the tubule fluid when high HCO-3 solutions were used as perfusate. These data suggest that chloride/formate exchange with recycling of formic acid by nonionic diffusion represents a mechanism for active, electroneutral NaCl reabsorption in the proximal tubule.